Penoscrotal edema: a case report and literature review - Tian Lin; Yun-Zhi Lin; Yu-Peng Wu; Ting-Ting Lin; Dong-Ning Chen; Yong Wei; Xue-Yi Xue; Ning Xu (BMC Urology, 2019)
Abstract Background Penoscrotal edema is typically caused by lymphatic obstruction, which can have both primary and secondary causes. Studies describing congenital penoscrotal edema are rare. Surgery can be divided into two types: The first approach involves extensive removal of diseased tissue and tissue reconstruction. The second approach is removal of the lesions and creating additional lymphatic vascular anastomoses. Case presentation We present a case report of a 15-year-old patient with recurrent penoscrotal edema and swelling of both lower extremities. The literature were also reviewed to provide additional information. Physical examination revealed slow lymphatic reflux of the lower extremities and no obvious abnormalities in testicular morphology, bilaterally, or blood supply. Surgery was performed by excising the affected skin and subcutaneous tissue and the flaps was cut in the middle in Y shape to cover the penis and scrotum. Postoperative follow-up revealed wound integrity and patient satisfaction with the outcome. Conclusion Excision and reconstructive surgery are the primary treatments for penoscrotal edema. The majority of reported patients undergoing excision and reconstruction achieved satisfactory reshaping and improved their life quality.